Biogenic selenium nanoparticles with antifungal activity against the wood-rotting fungus Oligoporus pelliculosus - Pescuma, Micaela (2023)
Selenium nanoparticles (SeNPs) have antimicrobial and antifungal activity. SeNPs using Se resistant bacteria is a low cost and eco-friendly technology. Fungal contamination of wood during drying is one of the main causes of economic losses in the wood industry. The bacterium Delftia sp. 5 resistance to Se and its ability to produce SeNPs able to inhibit the growth of the wood brown-rotting fungus Oligoporus pelliculosus was analyzed. The strain showed an optimal SeNPs production when selenite concentration was 160 mg L−1. The SeNPs were spherical with an average size 192.33 ± 8.6 nm and a zeta potential of -41.4 ± 1.3 nm. The SeNPs produced by Delftia sp. 5 (33.6 ± 0.1 mg L−1 Se) inhibited the growth of O. pelliculosus in agar plates and in Nothofagus pumilio (Lenga) wood samples. Delftia sp. 5 SeNPs could be used for embedding lenga wood prior to drying for preventing the growth of the deteriorating fungi O. pelliculosus.